The complete mitogenome of Hong Kong paradise fish (Macropodus hongkongensis), an endemic freshwater fish in South China. Issue 2 (3rd July 2019) - Liu, Hongyi; Xu, Nan; Yang, Jing; Zhang, Qingzheng; Zuo, Ke; Lv, Fangzhong
Abstract: The first complete mitogenome of Hong Kong paradise fish ( Macropodus hongkongensis ) was determined in this study. The assembled mitogenome is 16, 494 bp and consisted of 13 protein-coding genes, 22 tRNAs, 2 rRNAs, and a control region. Nucleotide composition of the complete mitogenome is 30.6% A, 24.8% C, 14.8% G, and 29.8% T, with an A + T bias of 60.4%. The maximum-likelihood tree based on 13 protein-coding genes showed that M. erythropterus was the closest related species to M. hongkongensis .